MECHANISMS OF COIX SEED COMPOSITIONS IN THE TREATMENT OF SPLEEN DEFICIENCY AND WET DAMPNESS ZHENG - Han, Xiaochun; Xuming, Ji; Zhao, Haijun; Zhang, Yanan; Liu, Guowei; Wang, Yanfang; Zhao, Wenxiao; Wang, Shijun (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Coix seed has the functions of fortifying the spleen and inhibiting the dampness. However, it remains unclear which Coix seed compositions is responsible for these functions. Previous investigations have revealed that the main compositions of Coix seed are proteins, polysaccharides, oils and starches. The objectives of this study are to explore which is the most effective compositions in fortifying the spleen and examine how Coix seed works in regulating the water transport on the spleen deficiency and wet dampness (SDWD) rat model.Materials and Methods: The rats used were divided into (i) control group, (ii) model group, (iii) decoction group, (iv) protein group, (v) polysaccharide group, (vi) oil group and (vii) starch group. The urine volume, the drinking volume and the water loading index in each group were calculated. Agilent 8*60K array was used for microarray-based gene expression analysis. The differential mRNAs related to the transport activity were screened. qRT-PCR was used to validate the mRNA microarray.Results: The results demonstrated that all treatment groups could decrease the dampness of SDWD rats. mRNA microarray had significant effect on the protein group and the polysaccharide group in regulating the water transport, among which the most significant mRNA was Fabp6, Slc51a, Slc51b, Slc11a2, Slc4a10 and AQP3 respectively.Conclusion: The compositions of proteins and polysaccharides had the most significant effect in regulating the water transport of SDWD rat model. The contributing mRNA focused on Fabp, Slc and AQP family.